The Production and Stability Evaluation of Natural Lipstick - Juma'at, Nuramirah; Rahmat, Nur Aisyah; Hamidi, Siti Aisyah; Adnan, Norhidayu (Multidisciplinary Applied Research and Innovation, 2021)
From the past to the present, lipstick is one of the cosmetics that most useful and well-liked in women’s society. They wear lipstick today more for reasons of self-esteem and confidence. However, many lipsticks contained chemical ingredients that are toxic to bodies. This paper focused on producing natural lipstick that can help lips problem. Production of the natural lipstick were used extract banana, natural pigment, olive oil, lemon juice, beeswax, vitamin E oil, and unrefined shea butter. Most of them act as moisturizers among which are shea butter and beeswax, meanwhile the lemon juice and extract banana contain a high antioxidant that can help prevent free radicals. Next, there are several processes in making natural lipstick such as weighing, melting and mixing, moulding, and flaming. The 3 formulations of the lipstick were produced with different results but the best lipstick was selected by their standard values after several tests such as pH test, melting point, breaking point, skin irritation, and others. The formulation 3 of lipsticks was selected as the best lipstick. However, there have some factors which were affected the result evaluations of natural lipsticks.